1997
DOI: 10.1128/aem.63.10.3992-3994.1997
|View full text |Cite
|
Sign up to set email alerts
|

Ribotyping for strain characterization of Clostridium perfringens isolates from food poisoning cases and outbreaks

Abstract: Ribotyping was used to characterize 34 Clostridium perfringens strains isolated from 10 food poisoning cases and outbreaks over a 7-year period. Twelve different ribopatterns were generated by EcoRI digestion. In eight food poisoning cases and outbreaks, all of the ribotypes of each food and stool isolate were found to be identical. Two C. perfringens isolates showed unique patterns. Ribotyping was found to be a useful tool for determining the genetic relationship of C. perfringens isolates in the context of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…DNA was isolated using the guanidinium thiocyanate method of Pitcher et al [22] with modi¢cations [12]. Ensuing procedures were carried out as described previously [23]. The DNA probe was prepared from Escherichia coli 16S and 23S rRNA (Boehringer, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Ribotypingmentioning
confidence: 99%
“…DNA was isolated using the guanidinium thiocyanate method of Pitcher et al [22] with modi¢cations [12]. Ensuing procedures were carried out as described previously [23]. The DNA probe was prepared from Escherichia coli 16S and 23S rRNA (Boehringer, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Ribotypingmentioning
confidence: 99%
“…In this study, a convincing reproducibility was observed, as reported before for Cl. perfringens (Schalch et al 1997). The discriminatory index for ribotyping of Cl.…”
Section: Resultsmentioning
confidence: 99%
“…, Yersinia enterocolitica (Lobato et al 1998), and Cl. perfringens (Forsblom et al 1995;Schalch et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations